Penyuluhan dan Pendampingan pada Peserta Didik Sekolah Dasar Kartika XII-1 Manado tentang Jajanan Sehat - Kuhon, Frelly Valentino; Palandeng, Henry; Nelwan, Jeini Ester; Sumampouw, Oksfriani Jufri (Universitas Pahlawan Tuanku Tambusai, 2025)
Elementary school-age children are still easily persuaded by friends, the environment, advertisements, and the seduction of hawker sellers. Therefore, we make elementary school students as an educational target, so that they understand the importance of precision in buying snacks. The purpose of this activity is to find out the influence of counseling on the knowledge of SD Kartika XXI-1 students about healthy snacks at school. The method of implementation in this PkM activity is the counseling method for students of SD XXI-1 Kartika Jaya, Wanea District, Manado City. Counseling activities are a two-way communication process between communicators (extension workers) and communicators in an interaction. This activity will be carried out in May 2024, starting at 09.00 WITA. This health education activity is evaluated through knowledge change through direct questions and answers with students where the results are obtained that the students already understand about choosing healthy snacks, especially at school. The conclusion of this activity is that counseling activities can increase the knowledge of SD Kartika XXI-1 students about healthy snacks at school.